2015
DOI: 10.1371/journal.pone.0137106
|View full text |Cite
|
Sign up to set email alerts
|

A Food-Derived Flavonoid Luteolin Protects against Angiotensin II-Induced Cardiac Remodeling

Abstract: Oxidative stress has been implicated in cardiac remodeling (cardiac fibrosis and hypertrophy), which impairs cardiac function and metabolism; therefore, it is anticipated antioxidative compounds will have protective properties against cardiac remodeling. Luteolin (3’,4’,5,7-tetrahydroxyflavone), a widely distributed flavonoid found in many herbal extracts including celery, green pepper, perilla leaves and seeds, and chamomile, is a known to be a potent antioxidant and was previously demonstrated to exert an an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…epigallocatechin gallate (EGCG), luteolin, kaempferol) as cardioprotective . Luteolin for instance protects against ischemia/reperfusion‐induced myocardial injury as well as angiotensin II‐induced cardiac remodeling . In addition to this, some of our compounds have previously been implicated in the regulation of PTMs that include phosphorylation, acetylation, and methylation in other chronic disease states .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…epigallocatechin gallate (EGCG), luteolin, kaempferol) as cardioprotective . Luteolin for instance protects against ischemia/reperfusion‐induced myocardial injury as well as angiotensin II‐induced cardiac remodeling . In addition to this, some of our compounds have previously been implicated in the regulation of PTMs that include phosphorylation, acetylation, and methylation in other chronic disease states .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, reports have highlighted a role for some of our identified compounds (e.g. epigallocatechin gallate (EGCG), luteolin, kaempferol) as cardioprotective . Luteolin for instance protects against ischemia/reperfusion‐induced myocardial injury as well as angiotensin II‐induced cardiac remodeling .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has demonstrated that luteolin has a certain therapeutic effect on cardiovascular disease, including preventing ischemia/reperfusion injury in adult rats (14) and sodium fluoride-induced hypertension in rats (28), ameliorating inorganic mercury-induced cardiac injury in rats (29), decreasing high-carbohydrate/high-fat diet-induced myocardial inflammation (15), and improving angiotensin II-induced cardiac remodeling by decreasing oxidative stress (16). SIc, first described by Parker et al (30) in 1984, is a complication of severe sepsis and septic shock characterized by an invertible myocardial depression.…”
Section: Discussionmentioning
confidence: 99%
“…These cardiovascular protective effects of luteolin may be due to its antioxidant activities. For example, luteolin can improve angiotensin II-induced cardiac remodeling by decreasing oxidative stress (16). While increasing evidence shows that luteolin exerts cardiovascular protective effects, the possible beneficial effects of luteolin on SIC have not yet been fully clarified.…”
Section: Introductionmentioning
confidence: 99%
“…It stimulates pro-fibrotic cytokine transforming growth factor β (TGFβ1) expression ( Rosenkranz, 2004 ). Nakayama et al (2015) clearly demonstrated that in Ang II-induced hypertension rats, TGF β1, CTGF, Nox2, and Nox4 gene expression were increased and oral pretreatment with a high-luteolin diet restored the above indices, and also suppressed H 2 O 2 -induced TGFβ1 expression. Food-derived Lut may be a therapeutic strategy through the inhibition of Ang II-induced cardiac remodeling ( Nakayama et al, 2015 ).…”
Section: Introductionmentioning
confidence: 86%